Search for medium effects using jets from bottom quarks in PbPb collisions at sNN=5.02TeV - KAYA, MİTHAT (My University, 2023)
The first study of the shapes of jets arising from bottom (b) quarks in heavy ion collisions is presented. Jet shapes are studied using charged hadron constituents as a function of their radial distance from the jet axis. Lead-lead (PbPb) collision data at a nucleon-nucleon center-of-mass energy of sNN=5.02TeV were recorded by the CMS detector at the LHC, with an integrated luminosity of 1.69nb−1. Compared to proton-proton collisions, a redistribution of the energy in b jets to larger distances from the jet axis is observed in PbPb collisions. This medium-induced redistribution is found to be substantially larger for b jets than for inclusive jets.
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (SCI); FİZİK, NÜKLEER; Natural Sciences (SCI); PHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; b jets; Beauty quark; CMS; Heavy ion; Jet quenching; QGP